= Presidential Decree Law No. 13 of the year 2014 on Amending Some Provisions of the Agriculture Law promulgated by Law No 53/1966 قرار رئيس الجمهورية بالقانون رقم 13 لسنة 2014 بتعديل بعض أحكام قانون الزراعة رقم 53 لسنة 1966 / Presidency - Egypt. Presidency (2025)
Presidential Decree-Law No. 13 of the year 2014 On Amending some Provisions of the agriculture law promulgated by law no. 53 of the year 1966 – قرار رئيس الجمهورية بالقانون رقم 13 لسنة 2014 بتعديل بعض أحكام قانون الزراعة الصادر بالقانون رقم 53 لسنة 1966